Technology Acceptance Model Toward Pandawa Service at the Social Security Administrative Body for Health Depok - Yoam, Crefinda Hanna Ananda; Pujiyanto; Atik Nurwahyuni; Damaryanti, Laksmi (Jurnal Jaminan Kesehatan Nasional, 2025)
Digital transformation has become a prominent topic in the era of globalization. Despite the growing digital transformation trend, many health service users in Indonesia still prefer face-to-face interactions, indicating a gap in digital literacy and service adoption. In response to this issue, the Social Security Administrative Body for Health launched a digital administrative service called Pandawa (Administrative Service via WhatsApp). This study aims to explore the perceptions of National Health Insurance participants who visited Social Security Administrative Body for Health Depok in 2025, focusing on the perceived ease of use and usefulness of the Pandawa service. The research employs a quantitative approach using the Technology Acceptance Model (TAM) through a cross-sectional study design. The secondary data used in this study consists of participant visits to the agency in 2024. Primary data will also be needed through distributed questionnaires. The sample consists of 109 National Health Insurance participants who are users of the Pandawa service and visited the agency during the study, conducted in February 2025. The analysis techniques of the research used the Chi-Square Test and the Binary Logistic Regression Test. The multivariate analysis shows that age, education, perceived ease of use, perceived usefulness, and attitude are significantly related to the intention to use the Pandawa service, with attitude being the dominant factor. Meanwhile, sex does not show a significant relationship to the intention to use the Pandawa service. Overall, user acceptance of the Pandawa service is relatively good, although further improvements in service quality are necessary to optimize its implementation.